2011
DOI: 10.5430/ijfr.v2n1p57
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cost-Push and Monetary Factors on GDP Deflator: Empirical Evidence from the Economy of Pakistan

Abstract: The central objective of this paper is to find the validity of cost-push and monetary factors on GDP deflator through empirical analysis. The empirical analysis has been conducted by using the technique of Ordinary Least Square using annual data for the period from 1971-72 to 2006-07. Before applying OLS the stationarity of the data was checked by Augmented Dickey Fuller (ADF) test. Regression analysis proves that both cost-push and monetary factors are influenced on wholesale price index. The monetary variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…This insight aligns with the notion that long-term debt typically elevates the cost of debt, thereby reducing a firm's profitability. These results are in harmony with prior investigations by Ahmad et al (2015), Mukras (2015), Javed (2015), Ilyukhin (2015), Singh and Bansal (2016), Dalci (2018), andDaryanto et al (2018).…”
Section: Discussionsupporting
confidence: 93%
“…This insight aligns with the notion that long-term debt typically elevates the cost of debt, thereby reducing a firm's profitability. These results are in harmony with prior investigations by Ahmad et al (2015), Mukras (2015), Javed (2015), Ilyukhin (2015), Singh and Bansal (2016), Dalci (2018), andDaryanto et al (2018).…”
Section: Discussionsupporting
confidence: 93%
“…The positive association was related to flow of cash due to higher and long-term debt, hence increasing the profitability of firms, but the other side of the coin is that the long-term debt also brings in high cost of debt, hence decreasing the firm's profitability. The current results are in accordance with the past studies of Ahmad et al (2015), Mukras (2015), Javed (2015), Ilyukhin (2015), Singh and Bansal (2016), Dalci (2018) and Daryanto et al (2018). Moreover, the result of moderation of debt finance between working capital and profitability is interesting.…”
Section: Discussionsupporting
confidence: 93%
“…There result support demand-side inflation. According to [26] money supply effects all indicators of inflation.…”
Section: Demand Side Channel Of Mtmmentioning
confidence: 99%
“…By using Johannes cointegration utilizing by [37] found that import of goods and services was the main reason of inflation. The study of [26] is when government expenditure are more than their revenue, the government takes deficit financing, therefore, prices level increases and also inflation occurs. Moreover, inflation expectation increases if upgrade level of government debt.…”
Section: Cost Channel Of Mtmmentioning
confidence: 99%